Antiamnestic effect of new nicotinic acid derivatives - Victor V. Yasnetsov; Diana E. Kaurova; Sofia Ya. Skachilova; Evgeniy Yu. Bersenev (Belgorod National Research University, 2021)
Introduction: The search for new drugs for the prevention and treatment of vascular cognitive disorders continues to be a relevant task of pharmacology. In this regard, the aim of this work is to study the antiamnestic effect of five new nicotinic acid derivatives in comparison with the well-known drug mexidol (ethylmethylhydroxypyridine succinate) in animals. Materials and methods: The experiments were carried out on white male mice using conditioned passive avoidance reflex (CPAR). Electroconvulsive shock (ECS), scopolamine administration, and acute hypoxia in a hermetic chamber were used as amnesic effects. Testing for the safety of CPAR was performed 24 h after amnesic exposure. The new substances, reference drug mexidol, and a 0.9% sodium chloride solution (control group) were administered once intraperitoneally 60 min before mice training. Results and discussion: Three of the five new nicotinic acid derivatives, LKhT 4-19 (100 mg/kg), LKhT 6-19 (25, 50, and 100 mg/kg), and LKhT 7-19 (100 mg/kg), have antiamnestic properties on models of amnesia in mice induced by ESC, scopolamine, and acute hypoxia in a hermetic chamber. At the same time, the most efficient substance - LKhT 6-19 - exceeds the reference drug mexidol on all three models used. In addition, this compound is also more efficient than two other new compounds, LKhT 4-19 and LKhT 7-19, on the model of ESC-induced amnesia and LKhT 7-19 on the scopolamine-induced amnesia model. Conclusion: Compound LKhT 6-19 is promising for further advanced preclinical studies as a potential drug with antiamnestic activity. Graphical abstract: